PENDISTRIBUSIAN UANG KEMBALIAN KONSUMEN ATAS TRANSAKSI JUAL BELI PRODUK DI PASAR SWALAYAN UNTUK PROGRAM DONASI - Irene Cantika Aritonang (2023)
The purpose of this research is to see the validity of the agreement on cashback from product transactions in supermarkets that are directed to Donation Program donations. Several supermarkets in their operations are often found distributing change as donations for the Donation Program. The results of the research findings, in practice this action often occurs irregularities in the form of violations of consumers' right to return money in terms of voluntarily collecting them without a transparent explanation. The method used in this study is a normative juridical legal research method supported by primary data in the form of observation and interviews (depth interviews). In this study, it will be discussed whether the distribution of consumer refunds from buying and selling products in supermarkets for donations to donation programs is legal and fair (fairness). Then how is the implementation of the distribution of consumer change from buying and selling transactions of these products from the point of view of regulations related to Consumer Protection, Collection of Money or Goods, and Implementation of Collection of Money or Goods. The conclusion of the study is that the distribution of consumer refunds into donations to donation programs is a legitimate distribution, but must be carried out based on agreement, good faith and transparency, accountable to provide fairness in accordance with relevant laws and regulations and not harm one another.